An efficient solid-phase strategy for total synthesis of naturally occurring amphiphilic marine siderophores: amphibactin-T and moanachelin ala-B. Issue 16 (25th March 2015) - Cherkupally, Prabhakar; Ramesh, Suhas; Govender, Thavendran; Kruger, Hendrik G.; de la Torre, Beatriz G.; Albericio, Fernando
Abstract : The first total synthesis of the naturally obtainable marine siderophores amphibactin-T and moanachelin ala-B on solid-phase using standard Fmoc-chemistry is reported. Abstract : Microorganisms such as bacteria, fungi and some plants secrete an abundance of suites of low molecular weight, high-affinity iron(iii )-chelating acylated siderophores. The peptide composition of a suite of amphiphilic siderophores generated by a Vibrio species, isolated from oligotrophic open ocean water, contained the same iron(iii )-scavenging polar head group and is attached to a fatty acid. In the present study, we report the first total synthesis of the naturally obtainable marine siderophores amphibactin-T and moanachelin ala-B on solid-phase using standard Fmoc-chemistry. Furthermore, we discuss the preparation of orthogonal protected Orn amino acid ' N α -Fmoc- N δ -(acetyl)- N δ -(benzoyloxy)-ornithine' [Fmoc-Orn(Ac, OBz)-OH], which is the most important constructive building block for amphibactin and moanachelin siderophores syntheses. The applications of this Orn unit on solid-phase have also been discussed.